2020
DOI: 10.1111/hae.14113
|View full text |Cite
|
Sign up to set email alerts
|

Early wound complications after orthopaedic surgery for haemophilia: What can we do more

Abstract: Background: The characteristics of the haemophilia may endanger the patient with haemophilia (PWH) to higher ratio of wound complication, even lead to the refractory wound problem. The early wound complication in PWH has not been well studied in literature. Methods: Between the period from 2002 to 2018, 250 patients underwent 323 elective orthopaedic surgical procedures for the treatment of haemophilic musculoskeletal disorders. The medical records were retrospectively reviewed. The patients were evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Once in contact with wound exudate, the hydrocolloid particle (CMC sodium carboxymethylcellulose) in the dressing swells after absorbing the exudate, forms a soft, cohesive hydrogel that allows it to absorb the wound exudate while locking it in within the gel, avoiding the risk of exudate leakage as well as the wound skin. Intrasite gel also creates a moist environment conducive to wound healing [20][21][22]. e results of this study showed that after treatment, the positive rate of wound bacterial culture in the observation group was significantly lower than that in the control group.…”
Section: Discussionmentioning
confidence: 67%
“…Once in contact with wound exudate, the hydrocolloid particle (CMC sodium carboxymethylcellulose) in the dressing swells after absorbing the exudate, forms a soft, cohesive hydrogel that allows it to absorb the wound exudate while locking it in within the gel, avoiding the risk of exudate leakage as well as the wound skin. Intrasite gel also creates a moist environment conducive to wound healing [20][21][22]. e results of this study showed that after treatment, the positive rate of wound bacterial culture in the observation group was significantly lower than that in the control group.…”
Section: Discussionmentioning
confidence: 67%
“…For an HPT with a large bone defect and/or pathological fracture, or when more than one-third of the bone diameter was involved, the HPT was curetted and osseous reconstruction was performed. For an HPT with an infected open wound, HPT excision and debridement were performed, followed by vacuum sealing drainage for wound management and infection eradication 19 . Amputation was performed only in patients with massive destruction of host tissue and in cases complicated by a refractory infection or wound problem.…”
Section: Treatment Strategymentioning
confidence: 99%
“…T H E J O U R N A L O F B O N E & JOINT SURGERY d J B J S . O R G VOLUME 105-A d N U M B E R 8 d A P R I L19, 2023 …”
mentioning
confidence: 99%
“…Persons with hemophilia A (HA) may require surgical procedures to treat conditions both related (eg, insertion and removal of central venous access devices [CVADs], orthopedic surgery for the treatment of joint damage) and unrelated to the hemophilia. During the perioperative period, enhanced hemostatic support is essential to prevent bleeding complications, inadequate wound healing, and infections [ 1 ].…”
Section: Introductionmentioning
confidence: 99%